Design and operation of a 20 kWth fluidised bed combustor for biomass oxy-fuel combustion - Sher, Farooq (2017)
Due to growing concerns about climate change, the heat and power sector is continuously facing challenges to reduce CO2 emissions. Carbon capture and storage (CCS) is one of the short-medium term measures that can mitigate CO2 emissions emitted from fossil fuels utilisation. Oxy-fuel combustion is a promising technology for CSS that can be integrated into the new and the current fleet of power plants. Biomass is a carbon neutral renewable source of energy that can replace fossil fuels. If the biomass is utilised as a fuel in oxy-fuel combustion it could lead even to negative CO2 emissions. Although the sintering and agglomeration problems associated with the combustion of non-woody biomasses in the fluidised beds are still major issues, fluidised beds have emerged as one of the best among the other proven biomass combustion technologies, mainly due to their fuel flexibility, low SOx and NOx emissions. However, oxy-fuel combustion technology in fluidised beds is in the early stages of development and still needs a lot of research for improvement before its application on full-scale power plants.